Women seek greater role in rebuilding the Central African Republic - Zipporah Musau (Africa Renewal, 2016)
The current security and humanitarian situation in the Central African Republic (CAR) is dire—a reality that has prompted women of the CAR to make one urgent request to the international community: to be included in the conflict-stricken country’s ongoing peace-building process.